Epigenetic Alterations in Oncogenesis - Karpf, Adam R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The purpose of this book is to provide an up to date review of the nature and consequences of epigenetic changes in cancer. Epigenetics literally means (3z(Babove(3y (Bgenetics, and consists of heritable gene expression or other phenotypic states not accounted for by DNA base sequence. Epigenetic changes are now known to make a large contribution to various aspects of tumorigenesis. These changes include alterations in global and promoter specific DNA methylation, activating and repressive histone modifications, and changes in higher order chromatin structures. Each of these topics will be covered in this book.s
Preface -- Section I: Epigenetic Marks and Mechanisms -- DNA methyltransferases (DNMTs), DNA damage repair, and cancer -- DNA hypomethylation and hemimethylation in cancer -- Ten Eleven Translocation (TET) Enzymes and 5-hydroxymethylation in Mammalian Development and Cancer -- Altered histone modifications in cancer -- Nucleosome occupancy and gene regulation during tumorigenesis -- Section II: The Impact of Epigenetic Alterations on Cancer Biology -- Epigenetic regulation of miRNAs in cancer -- DNA hypomethylation and activation of germline-specific genes in cancer -- APC and DNA demethylation in cell fate specification and intestinal cancer -- Epigenetic changes during cell transformation -- Epigenetic reprogramming of mesenchymal stem cells -- Section III: Clinical Implications and Analysis Methods -- Environmental toxicants, epigenetics, and cancer -- Blood derived DNA methylation markers of cancer risk -- Epigenetic therapies in MDS and AML -- Epigenetic targeting therapies to overcome chemotherapy resistance -- Methods for cancer epigenome analysis -- Index.
Keywords: Medicine; Oncology; Human genetics; Biomedicine; Cancer Research; Human Genetics; Oncology